La aplicación del juego y su incidencia en el desarrollo de la creatividad de los niños y niñas del primer grado de la escuela de educación general básica “Provincia De Loja”, del cantón Joya de los Sachas, provincia de Orellana, periodo 2013 – 2014 - Cango Castillo, Rosalina Margarita (2014)
The present titled investigation: THE APPLICATION OF THE GAME AND THEIR INCIDENCE IN THE DEVELOPMENT OF THE CREATIVITY OF THE CHILDREN AND GIRLS OF HIGH SCHOOL, FIRST GRADE OF BASIC GENERAL EDUCATION OF THE SCHOOL " PROVINCIA DE LOJA" OF THE CANTON JOYA DE LOS SACHAS, COUNTY DE ORELLANA, PERIOD 2013 - 2014. It is structured based on the effective Limits of Graduation in the National University of Loja. The general objective that guided the investigative process was: To analysis if the application of the Game impacts in the Development of the Creativity of the children and girls of First Grade of Basic General Education of the School "Provincia de Loja" of the Canton Joya de los Sachas, County of Orellana, Period 2013 - 2014. The used methods were: Scientific, Inductive, Deductive and Statistical Model. The applied techniques were the following ones: The Survey applied the teachers of High school, First Grade of Basic General Education of the school "Welded Francisco Arturo Colonel", with the purpose of obtaining information on the application of the Game in the daily work with the children and girls; and, the Guide of Observation applied the children and girls for determine the Development of the Creativity. Of the application of the Survey to the teachers was verified that: 100% applies activities of Game in the daily day of work with the children and girls; and that the game types that apply are: 100% plays symbolic and free; and 50% the directed game and of rules. The application of the Game in the daily day of work is a privileged activity for the children and girls, because when the children play they exercise its body in growth, they learn how to control and to coordinate their muscles, the articulations, the movements, but also, it stimulates the intelligence the creativity and the emotions. In the same way it was determined that: 67% of children and investigated girls show a Development of the Very Satisfactory Creativity; 27% Satisfactory; and 6% Not very Satisfactory. For what you can determine that a low percentage of children and girls that require the area of Development of the Creativity exists it is stimulated; since the development of this area will allow that the children and girls are critical that they can express their own ideas and at the same time have a high self-esteem that facilitates them an appropriate development inside the means that surrounds them.